Peranan Kelompok Tani Anugrah Satu Dalam Pengembangan Komoditi Kentang Di Desa Linelean Kecamatan Modoinding Kabupaten Minahasa Selatan - Tulong, Greity Fitria; Porajouw, Oktavianus; Maweikere, Audrey Julia Maria (AGRI-SOSIOEKONOMI, 2024)
This study aims to describe the role of the "Anugrah Satu" farmer group in developing the potato commodity. This research was conducted in Linelean Village, Modoinding District, South Minahasa Regency, planned for 3 months, namely July to September 2023. The data collection method used primary and secondary data. Data collection in this study was carried out in 3 stages, namely observation, interviews and documentation. The population in this study were all members of the Anugrah Satu farmer group totaling 20 people. The sample was taken as a whole farmer group member or saturated sample. Data was measured with a Likert scale, then analyzed using the Role Level Index. The results showed that based on the results of the study it can be concluded that the level of role of the Anugrah Satu farmer group in the development of potato commodities in Linelean Village, Modoinding Subdistrict, South Minahasa Regency is classified in the Very Role category, with an index number of 85.91%. The Anugrah Satu farmer group can still increase its role in the development of potato commodities to a higher level at an index number of 90-95%.